2015
DOI: 10.1021/mp5005838
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Inhibition of Intestinal Glucuronidation in Enhancing the Oral Bioavailability of Resveratrol by Labrasol Containing Nanoemulsions

Abstract: Nanoemulsions have been developed for the oral delivery of poorly bioavailable phenolic compounds that are sensitive to intestinal glucuronidation. However, little is known about the contribution of UDP-glucuronosyltransferase (UGT) inhibitory excipients in nanoemulsions toward the inhibition of intestinal glucuronidation and the consequent enhanced bioavailability. In this study, Labrasol but not poloxamer 188 (F68) was found to inhibit the glucuronidation of resveratrol (RES), a model phenolic compound, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 55 publications
2
57
1
Order By: Relevance
“…For avoiding the enzymatic barrier, however, the effect of Labrasol on enzymatic activity must be considered. It is reported that Labrasol inhibits intestinal UDP-glucuronyl transferase (33). Although the effect of Labrasol on the activities of insulin degrading enzymes in the intestine is not clear, the condensed Labrasol in a dimple may inhibit them.…”
Section: Discussionmentioning
confidence: 99%
“…For avoiding the enzymatic barrier, however, the effect of Labrasol on enzymatic activity must be considered. It is reported that Labrasol inhibits intestinal UDP-glucuronyl transferase (33). Although the effect of Labrasol on the activities of insulin degrading enzymes in the intestine is not clear, the condensed Labrasol in a dimple may inhibit them.…”
Section: Discussionmentioning
confidence: 99%
“…The latter involve liposomal formulations (Mukherjee et al, 2011) and nanoemulsions (Zhou et al, 2015), while lead structure optimization focused on higher hydroxylated (Murias et al, 2004), halogenated (Lee et al, 2003), or methylated (Cardile et al, 2007) analogs of resveratrol.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The present study and our previous one (Sun et al, 2015b) indicated that cellular conjugation is regulated by efflux transporters. Hence, the inhibition of both enzymes and transporters represented a novel and promising strategy to enhance the oral bioavailability of drugs undergoing extensive conjugation, although the inhibition of enzyme activity alone showed potential in enhancing resveratrol bioavailability (Zhou et al, 2015).…”
mentioning
confidence: 99%